(untitled) (World Science, 2021)
Defect in the function of pancreatic cells is one of the key pathophysiological factors in type 2 diabetes, in particular, an imbalance between the secretion of insulin and glucagon, as well as a decrease in the efficiency of converting proinsulin into insulin, often observed. The aim of the work was to compare the characteristics of the secretory function of pancreatic alpha and beta cells in 43 patients with decompensated type 2 diabetes mellitus when using new classes of anti-diabetic drugs: glucagon-like peptide receptors agonists (GLP1ra) and inhibitors of the sodium-glucose transporter-2 (SGLT2i). Long-term treatment with these drugs (for 12 months) contributed to the normalization of the HbA1c level and a decrease in the % of visceral fat, as well as a decrease in the glucagon level compared to the baseline level. In both groups of patients, subgroups with high and low proinsulin levels have been identified. Under the influence of GLP1ra therapy, in patients of the low proinsulin subgroup, serum concentration of proinsulin and C-peptide significantly decreased, indicating a decrease in insulin secretion and a possible reduce in adaptive release of proinsulin as a result of glycemia decrease. Among patients treated with SGLT-2i, high pre-treatment proinsulin levels associated with higher glucagon and C-peptide concentrations comparing the low proinsulin subgroup. After 12 months of treatment, no significant changes in the concentration of glucagon, C-peptide and proinsulin were observed in both subgroups of patients treated with SGLT2i.